2018
DOI: 10.1038/s41431-018-0203-6
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing in intellectual disability; cost before and after a diagnosis

Abstract: Clinical application of whole-exome and whole-genome sequencing (WES and WGS) has led to an increasing interest in how it could drive healthcare decisions. As with any healthcare innovation, implementation of next-generation sequencing in the clinic raises questions on affordability and costing impact for society as a whole. We retrospectively analyzed medical records of 370 patients with ID who had undergone WES at various stages of their diagnostic trajectory. We collected all medical interventions performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 21 publications
4
50
2
2
Order By: Relevance
“…WES includes all of the coding exons of the genome, which facilitates gene-panel analysis without redesign of the experiment in case of updates. A WES-based test combined with variant analysis aimed at the genes of interest is known to have multiple advances over targeted gene-panel capture and sequencing (83): (1) newly identified genes can easily be added to the analysis without adjustment and validation of the laboratory flow-because the nephrogenetics field is evolving fast, with causal genes being identified on a regular basis, a flexible approach like WES facilitates rapid test updates; (2) gene-panel analysis from WES data prevents the identification of incidental findings; (3) data on the full exome is available and can be released for further investigation in case the molecular cause has not been identified, leading to a higher diagnostic yield (84); and (4) WES results in a considerable reduction of diagnostic time and healthcare costs, especially when applied early in the diagnostic process (80,85).…”
Section: Current Molecular Diagnostic Tools For Patients With Congenimentioning
confidence: 99%
“…WES includes all of the coding exons of the genome, which facilitates gene-panel analysis without redesign of the experiment in case of updates. A WES-based test combined with variant analysis aimed at the genes of interest is known to have multiple advances over targeted gene-panel capture and sequencing (83): (1) newly identified genes can easily be added to the analysis without adjustment and validation of the laboratory flow-because the nephrogenetics field is evolving fast, with causal genes being identified on a regular basis, a flexible approach like WES facilitates rapid test updates; (2) gene-panel analysis from WES data prevents the identification of incidental findings; (3) data on the full exome is available and can be released for further investigation in case the molecular cause has not been identified, leading to a higher diagnostic yield (84); and (4) WES results in a considerable reduction of diagnostic time and healthcare costs, especially when applied early in the diagnostic process (80,85).…”
Section: Current Molecular Diagnostic Tools For Patients With Congenimentioning
confidence: 99%
“…One Dutch study retrospectively examined Whole Exome Sequence data for 370 patients with ID finding a diagnostic yield of 35 and an 80% reduction in healthcare costs per patient after genetic testing regardless of diagnostic result (Vrijenhoek et al, ). However, studies using patient reported outcome measures are sparse.…”
Section: Literature Review Of Genetic Testing For People With Intellementioning
confidence: 99%
“…Along with the decreasing cost of sequencing, these improvements have facilitated the transition of genomic testing from a research endeavour to clinical diagnosis. There is limited economic evidence supporting this transition 6 11–16. The available studies that attempt to determine the cost-effectiveness of genomic testing1 12 17 18 do not employ standard methods for the economic evaluation of health technologies,19 relying on simplified assumptions to estimate cost-effectiveness, largely due to lack of data to populate the models 20 21…”
Section: Introductionmentioning
confidence: 99%